2011
DOI: 10.5402/2011/869273
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antihyperglycemic Activity of Citrus limetta Fruit Peel in Streptozotocin-Induced Diabetic Rats

Abstract: The present paper aims to evaluate antihyperglycemic activity of methanol extract of Citrus limetta fruit peel (MECL) in streptozotocin-induced (STZ; 65 mg/kg b.w.) diabetic rats. Three days after STZ induction, diabetic rats received MECL orally at 200 and 400 mg kg−1 body weight daily for 15 days. Glibenclamide (0.5 mg kg−1 p. o.) was used as reference drug. Blood glucose levels were measured on 0th, 4th, 8th, and 15th days of study. Serum biochemical parameters namely, SGOT, SGPT and ALP were estimated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…36 During PPE treatment there was significant reduction of FBG level progress till the end of the study compared to both control groups (p<0.05) whereas comparable to that obtained by treatment with standard plant (Table 3). The two major flavonoids of citrus maxima are naringenin and hesperidin are proven to be hypoglycemic agents and their hypoglycemic activity is mediated by their ability to inhibit intestinal αglycosidase activity which is a key enzyme of carbohydrate digestion located on intestinal cells, thereby delaying the absorption of carbohydrates in diabetic animals (Jung UJ et al 2004, KnuduSen S et al 2011 suggested that hesperidin may have the ability to protect pancreatic Beta cell from STZ actions and restore their ability to secret insulin. 37,38 Published data show wide phytochemical composition and pharmacological action of citrus maxima fruits.…”
Section: Discussionmentioning
confidence: 99%
“…36 During PPE treatment there was significant reduction of FBG level progress till the end of the study compared to both control groups (p<0.05) whereas comparable to that obtained by treatment with standard plant (Table 3). The two major flavonoids of citrus maxima are naringenin and hesperidin are proven to be hypoglycemic agents and their hypoglycemic activity is mediated by their ability to inhibit intestinal αglycosidase activity which is a key enzyme of carbohydrate digestion located on intestinal cells, thereby delaying the absorption of carbohydrates in diabetic animals (Jung UJ et al 2004, KnuduSen S et al 2011 suggested that hesperidin may have the ability to protect pancreatic Beta cell from STZ actions and restore their ability to secret insulin. 37,38 Published data show wide phytochemical composition and pharmacological action of citrus maxima fruits.…”
Section: Discussionmentioning
confidence: 99%
“…The peels are rich in pectin which is known to possess blood sugar lowering and cholesterol lowering properties 8 . Sriparna et al,9 demonstrated the antihyperglycemic effect and antioxidant property of C. maxima leaf in streptozotocin induced diabetic rats. Similarly, a previous study 10 has shown that the fruit juice of Shaddock (C.maxima) possess hypoglycemic and hypocholesterolemic activities.…”
Section: Research Articlementioning
confidence: 99%
“…Further, diets rich in citrate contents are commonly prescribed for stone prevention (Agarwal et al, 2011). In addition to that, Citrus fruits and their peels are found to help in improving various metabolic and inflammatory disorders attributing to the abundance in its bioactive compounds (Kundusen et al, 2011;Sood et al, 2010). Hence, this study was designed to investigate the efficacy of LP extract in experimentally induced hyperoxaluric animals.…”
Section: Introductionmentioning
confidence: 99%